634. Implementation of a medical education intervention to improve acceptance of HIV-positive donors for transplant at a tertiary care hospital. (15th December 2022) - Swaminathan, Neeraja; Hemmige, Vagish; Czeresnia, Jonathan Mamber; Muggia, Victoria; Azzi, Yorg; Akalin, Enver; Raees, Harith; Al Anssari, Haider
Abstract: Background: The HIV Organ Policy Equity Act (HOPE Act) was enacted in the US on November 21, 2013. HIV patients have a higher waitlist mortality and decreased access to transplant compared to HIV negative controls. The HIV Organ Policy Equity Act (HOPE Act) was a major step towards increasing the donor pool, but utilization of organs through the act has been less than initially anticipated.. Our own institution performed only one HIV D+/R+ transplant in the first four years of the trial despite a significant number of HIV+ patients on the waitlist. Table Figure summarizing perceived barriers and targeted interventions. Rate of HOPE transplants impacted positively by intervention Rate of HOPE transplants impacted positively by intervention Methods: Monthly multidisciplinary meetings were set up. The agenda included discussing all offers, risks/benefits in a standardized format. Didactic sessions were conducted to address identified barriers to accepting HIV+ organs (Figure 1). HOPE consultants from experienced larger-volume centers were invited as guests. Results: In the 15 months since this intervention was implemented, there have been 7 HIV D+/R+ transplants including a heart-kidney transplant. While the overall rate of transplant didn't change in a statistically significant way pre and post intervention for patients the rate of HOPE transplants increased significantly (Figure 2). Conclusion: Making organs from HIV-positive donors available for donation does not mean they will be used. Intensive provider education can improve organ acceptance rates and help fulfill the promise of the HOPE act. Disclosures: Vagish Hemmige, MD, Merck: Grant/Research Support.